Climate-Smart Agriculture in Grenada - Halliday, Andrew; Medellín, Claudia; Nowak, Andreea C.; Lizarazo, Miguel; Imbach, Pablo; Zavariz-Romero, Beatriz; Prasodjo, Rauf; Baca, María; Argote, Karolina; Cervantes, C; Louman, Bastian; Jarvis, Andy; et al. (2014)
The climate-smart agriculture (CSA) concept reflects an ambition to improve the integration of agriculture development and climate responsiveness. It aims to achieve food security and broader development goals under a changing climate and increasing food demand.